Development of dynamic layout model for poundo yam flour processing plant. Issue 1 (1st January 2017) - Ayodeji, S.P.; Adeyeri, M.K.; Ogunsua, A.
Abstract: A documented poundo yam process plant that produces 12.25 kg of poundo yam within 315.04 min was studied so as to address its associated problems. It was found that its production capacity is limited due to process time delay of 77 and 216 min experienced at the parboiling and drying section respectively. This informed the need to design a dynamic facility layout to increase production capacity, introduce flexibility of material flow through the process plant and manage effectively material flow through the process plant. In order to achieve this, a software called poundosim was developed using necessary design model equations and data. This will assist in forecasting material flow above the static reference frame of the production facility, and iteratively generate the optimal machine configuration within cost constraint, thereby preventing unending increase of service points at the regions of bottlenecks and ensuring economic viability of the entire processing plant. The successful deployment of the developed poundosim using input of values within the range of 12.25–134.75 kg at an increment of 12.25 kg shows a considerable decrease in the total process time at optimal machine configuration compared with the initial reference machine configuration. Thus, the developed model does prove useful for process plant which has similar attributes with poundo yam flour processing plant as it takes machine configuration matrix and the economic implication of production capacity into consideration.